Issues of Establishing a Campus-wide Computational Grid Infrastructure in the GERANIUM Project - Por, L.Y.; Su, M.T.; Ling, T.C.; Liew, C.S.; Ang, T.F.; Phang, K.K. (2006)
A campus-wide grid and cluster infrastructure using the Rocks clustering software is established. The infrastructure, namely Grid-Enabled Research Network and Info-structure of University of Malaya (GERANIUM), comprises five distinct clusters located at different faculties and institutes. In this paper, the GERANIUM topology and architecture are presented, and issues and experiences concerned are discussed.